Impatiens xanthinoides (Balsaminaceae), a new species from Yunnan, China - Xiu-Zhen, Cai; Guang-Wan, Hu; Yi-Yan, Cong (Phytotaxa, 2015)
Impatiens xanthinoides (Balsaminaceae) sp. nov. from Yunnan Province, China is described and illustrated. This species is similar to I. xanthina and I. fugongensis in plant height, golden-yellow flowers, lateral sepals 2, stamen 5 with obtuse apex, and 5-carpellate ovary. However, it differs with that two species in the lower sepal obconic with red striae, dorsal petal glabrous, the lateral united petals stipitate with fan-shaped, apex acute lower lobes, and fusiform capsule. The detailed morphological characters, diagnostic comparisons, habitat and micromorphology of seeds and pollen grains under scanning electron microscope (SEM) are presented. According to the IUCN Red List Categories and Criteria, I. xanthinoides is assessed as Critically Endangered (CR B1a; B1b(ii)) because of its limited distribution rang and decline of mature individuals.